Parentinguistics: Authoritarian and Permissive Communication Styles in Parents' Expressive Speech Acts - Kurniawan Kurniawan (Institut Agama Islam Negeri (IAIN) Kendari, 2023)
In the world of parenting, there are various parenting styles. Each of these parenting styles has its own impact on children. Parenting style can be reflected in the way parents communicate with children. This study focuses on the relationship between authoritarian or permissive parenting styles on aspects of language, especially expressive speech acts. A qualitative descriptive pragmatic approach is applied in this study. The data in this study are in the form of textual sources from the film